Pengaruh Pendekatan Jelajah Alam Sekitar (JAS) Berbantuan Media Kebun Penduduk Sekitar Sekolah Terhadap Keaktifan dan Hasil Belajar Biologi - Ni Putu Widiasih; Ni Nyoman Parmithi; A.A.Istri Mirah Dharmadewi (Emasains : Jurnal Edukasi Matematika dan Sains, 2018)
This study aims to determine the effect of approach of nature roaming around assisted the inhabitant garden the around of the school media against of active and biology learning outcomes of students tenth grade of mathematics and science SMAN 1 Abiansemal. This study is quasi experiment. Design using are nonequivalent control grub design. The population were student tenth grade of mathematics and science SMAN 1 Abiansemal. The sample consisting of two class, the experiment group (X MIA 4) and control group (X MIA 3) chosen with simple random sampling technique. Data obtained is quantitative data in the from of value of active obtained by inquiry method and biology learning outcomes obtained by essay test then analyzed using the statistical method of t-test and MANOVA with SPSS 23.0 for windows. Based on the analysis obtained: (1) The are a significant effect of approach of nature roaming around assisted the inhabitant garden the around of the school media against of active of student, (2) The are a significant effect of approach of nature roaming around assisted the inhabitant garden the around of the school media against of biology learning outcomes of student, (3) The are a significant effect of approach of nature roaming around assisted the inhabitant garden the around of the school media against of active and biology learning outcomes of student simultaneous it can be concluded there are effect of approach of nature roaming around assisted the inhabitant garden the around of the school media against of active and biology learning outcomes of student tenth grade of mathematics and science SMAN 1 Abiansemal.